The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Sun, Cheng-He; Gozlan, Rodolphe Elie; Wu, Ting; Xue, Dan; Lao, Ye-Ling; Yu, Jian-Feng; Zeng, Xiao-Shu; Li, Sha; Hardouin, Emilie A.; Andreou, Demetra; Zhang, Qun (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources as well as to set up efficient protected area networks for the conservation of marine species. Here, we use extensive sampling of Sebastiscus marmoratus, a commercially important inshore rockfish with high site fidelity, to characterise their population’s genetic structure along the China-Japan coast and determine the effect of past geological and current biological-physical barriers on current genetic footprint. A 461 base pair fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographic locations and 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise Fst and AMOVA revealed significant genetic differentiation among populations. The Bayesian Skyline Plots and Neutrality statistics showed a sudden S. marmoratus population expansion around the Pleistocene. The Beibu Gulf group has the lowest mean number of pairwise differences, lowest significant genetic differentiation, lowest haplotype and nucleotide diversity and should be protected in priority in the future. Ocean currents, seascape discontinuity, geographic distance and ecological characteristics may play an important role in shaping the contemporary phylogeographic patterns and population structures of S. marmoratus.